2009
DOI: 10.1016/j.socscimed.2008.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to clinical research participation in a diabetes randomized clinical trial

Abstract: Little is known about how barriers to research participation are perceived, affected by or interact with patient characteristics, or how they vary over the course of a clinical trial. Participants (285) in the Renin-Angiotensin System Study (RASS), a randomized clinical primary prevention study of diabetic nephropathy and retinopathy at 2 Canadiana dn 1 US university, rated potential barriers to research participation yearly for 5 years. Baseline barriers rated as most adversely affecting participation were: m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…These findings support prior research that highlights patient preferences and demands of study participation as perceived barriers to patient participation in research (17,19,20). Importantly, Robiner et al (21) found significant correlation between protocol adherence and perceived barriers such as missing work, frequency of appointments/procedures, number of appointments/procedures, and access to study location in 978…”
Section: Discussionsupporting
confidence: 85%
“…These findings support prior research that highlights patient preferences and demands of study participation as perceived barriers to patient participation in research (17,19,20). Importantly, Robiner et al (21) found significant correlation between protocol adherence and perceived barriers such as missing work, frequency of appointments/procedures, number of appointments/procedures, and access to study location in 978…”
Section: Discussionsupporting
confidence: 85%
“…By contrast, most studies of willingness to participate in RCTs have addressed patients with common illnesses with multiple inexpensive therapies, such as diabetes, heart failure, or systemic hypertension [6,9,14]. These diseases are each characterized by more indolent progression, greater affordability and clearer efficacy of treatments, and greater prevalence, enriching the pool of eligible RCT participants and thereby making active-controlled trials more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these areas of divergence, the characteristics of the disease areas studied have varied considerably, from prevalent illnesses such as congestive heart failure [9] in which multiple known effective therapies exist, to rare cancers for which no known effective therapies are available [23]. Some general themes have emerged, which guide many patients’ decisions to enroll, including the time demands of the trials [6,7,14,16,18,21,24], the risks of disease recurrence or progressions [7,23], and fears of being assigned placebo [6,7,10,15,18,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Most interesting is the run-in phase in which possible participants are rejected who could put the success of the study at risk, e.g., by being nonadherent (Farmer 1999). Additionally, there are many barriers to patients' participation (Ross et al 1999;Robiner et al 2009), which lead to study results not representing the comparison group in the population. As a consequence, findings based on clinical studies cannot necessarily be adapted to real-world situations.…”
mentioning
confidence: 99%